ANALISIS FRAMING WACANA GENDER STEREOTYPING DALAM TRAILER FILM SERIAL BRIDGERTON MUSIM PERTAMA - Wibowo, Meriva Putri; Bezaleel, Michael; Pratiwi, Peni (AKSA: Jurnal Desain Komunikasi Visual, 2025)
During the COVID-19 pandemic, the Indonesian film industry experienced a significant decline in both the number of productions and revenue. One of the main contributing factors was the shift of audience behaviors, as viewers turned to video on -demand services, such as Netflix, which making them more selective and critical of audiovisual contents. Consequently, the competition to attract audience interest become more challenging and trailer plays a crucial role for influencing audience decisions to watch a film or series. In the trailer for the first season of Bridgerton, which incorporated a specific discourse on gender stereotyping that resonates with social issues nowadays, contributing to the series’ record-breaking viewership hours. Based on this phenomenon, this study aims to analyse the influence of promotion media, which is trailer containing particular discourses, in attracting audience interest to watch the series. This research will apply a qualitative method, utilizing data collection techniques, which are interviews and observations. The data obtained will be analyzed using the framing analysis approach developed by William Gamson and Andre Modigliani to uncover the meanings behind scenes in the trailer related to gender stereotyping discourse.